2016
DOI: 10.1017/s0022215116009555
|View full text |Cite
|
Sign up to set email alerts
|

Facial nerve anomalies in paediatric cochlear implant candidates: radiological evaluation

Abstract: Background: Pre-operative radiological identification of facial nerve anomalies can help prevent intra-operative facial nerve injury during cochlear implantation. This study aimed to evaluate the incidence and configuration of facial nerve anomalies and their concurrence with inner-ear anomalies in cochlear implant candidates.Methods: Inner-ear and concomitant facial nerve anomalies were evaluated by magnetic resonance imaging and temporal high-resolution computed tomography in 48 children with congenital sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In the current study, syndromes with known association with anomalous courses of the facial nerve (i.e., CHARGE syndrome, aural atresia) received up‐front HRCT, as an abnormal course of the facial nerve can create a tight and difficult access to the round window and, correspondingly, a challenging electrode implantation with increased risk of injury . At least four large reports have demonstrated an association between inner ear malformation and facial nerve anomaly, with a range of 0.3% to 23% facial nerve abnormality coexisting with an inner ear abnormality . Importantly, in each of these studies, no facial nerve anomalies were detected in children with normal inner ear structures.…”
Section: Discussionmentioning
confidence: 97%
“…In the current study, syndromes with known association with anomalous courses of the facial nerve (i.e., CHARGE syndrome, aural atresia) received up‐front HRCT, as an abnormal course of the facial nerve can create a tight and difficult access to the round window and, correspondingly, a challenging electrode implantation with increased risk of injury . At least four large reports have demonstrated an association between inner ear malformation and facial nerve anomaly, with a range of 0.3% to 23% facial nerve abnormality coexisting with an inner ear abnormality . Importantly, in each of these studies, no facial nerve anomalies were detected in children with normal inner ear structures.…”
Section: Discussionmentioning
confidence: 97%
“…Much has been written about displacement of the intracranial portion of the facial nerve as it pertains to neurotologic surgery, but little to nothing has been reported about aberrancy of the nerve in parotid surgery. Extensive review of the literature revealed several studies that have discussed the indications and surgical approach to deep lobe parotid lesions; however, there was no discourse regarding abnormal facial nerve position due to deep lobe lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Malformations of the inner ear are frequently accompanied by abnormal positions of the facial nerve, which increases the risk of facial nerve palsy during surgery [ 34 ]. The labyrinthine segment of the facial nerve may show an anterior and superior displacement.…”
Section: Pre-operative Imagingmentioning
confidence: 99%